Chemical agents and chemical terrorism - Patocka, J; Fusek, J (Central European journal of public health, 2004)
Chemical terrorism is a new threat to the security of mankind, which scale essentially exceeds the impact of use of the most modem firearms. At present time all over the world threats from different radical elements to use radioactive materials, potent poisonous substances and pathogenic microorganisms for terrorist purposes became more frequent. High-toxic chemical substances can fall in terrorist hands through wide range of sources. Potentially misused types of chemical compounds are discussed in this article.
Keywords: terorismus; Chemical Warfare Agents; Humans; Terrorism; chemické bojové látky; chemická válka; lidé; Chemical Warfare